2017
DOI: 10.21608/jpp.2017.39633
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Auxin Treatment on Growth and Physiological Traits in Two Sunflower Cultivars Under Saline Conditions.

Abstract: Salinity considered one of abiotic stress affected to crop productivity. The present investigation aimed to give insights about the effect of NaCl saline on two cultivars sunflower plants (Helianthus annuus. L) and determine the usefulness of increasing relative salt tolerance by auxin treatment. Different responses of two sunflower cultivars Sakha 53 and China and differently susceptible to salinity stress levels by NaCl treatment in hydroponic culture experiment were investigated. The cultivar more tolerant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…A significant (P< 0.05) differences between treated and control plants were only observed in IBA treatment (10 -4 g/l and 10 -3 g/l) at pre-flowering stage (Table 6). This is in agreement with the results of Zayed et al (2017) who reported that the plant height was significantly increased due to auxin treatments in two sunflower cultivars (Sakha 53 and China) grown under saline stress (120 mM NaCl). It has also been postulated that the application of Indole-3acetic acid (auxin) improved the length and dry matter yield of shoot on wheat plant (Youssef et al, 2020).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…A significant (P< 0.05) differences between treated and control plants were only observed in IBA treatment (10 -4 g/l and 10 -3 g/l) at pre-flowering stage (Table 6). This is in agreement with the results of Zayed et al (2017) who reported that the plant height was significantly increased due to auxin treatments in two sunflower cultivars (Sakha 53 and China) grown under saline stress (120 mM NaCl). It has also been postulated that the application of Indole-3acetic acid (auxin) improved the length and dry matter yield of shoot on wheat plant (Youssef et al, 2020).…”
Section: Resultssupporting
confidence: 93%
“…According to Mousavi et al (2016), the β-carotene content and cell growth of Dunaliella salina, were positively affected by indole-3-acetic acid at 1 μM. Zayed et al (2017) postulated that the growth parameters such as leaf area and shoot and root fresh and dry weight were increased in sunflower plant treated with indole-3-acetic acid (auxin). Assessment of the Responses of Chickpea (Cicer arietinum L.) to the Exogenous Application of Gibberellic Acid and Indole... No significant increase in flowers number between treated and control plants, was observed in different IBA phytohormone treatments (Table 6).…”
Section: Resultsmentioning
confidence: 99%
“…Since auxins contribute to plant growth regulation, they can alleviate the deleterious effects caused by abiotic stresses. For example, the application of 25 ppm IAA to sunflower ( Helianthus annuus L.) (cultivars Sakha53 and China) under salt stress (120 mM NaCl) resulted in the highest salt tolerance index values for shoot fresh biomass (161.96% and 188.62%), shoot dry biomass (229.52% and 201.66%), root fresh biomass (202.48% and 167.30%), root dry biomass (292.50% and 370.00%), leaf area (167.97% and 152.84%), shoot length (136.82% and 162.74%), and root length (168.08% and 169.70%) ( Zayed et al, 2017 ). In the same study, IAA supplementation had improved CAT activity (152% and 350%) and PPO (110% and 100%) ( Zayed et al, 2017 ).…”
Section: Interplay Of Plant Hormones In Conferring Abiotic-induced Ox...mentioning
confidence: 99%
“…For example, the application of 25 ppm IAA to sunflower ( Helianthus annuus L.) (cultivars Sakha53 and China) under salt stress (120 mM NaCl) resulted in the highest salt tolerance index values for shoot fresh biomass (161.96% and 188.62%), shoot dry biomass (229.52% and 201.66%), root fresh biomass (202.48% and 167.30%), root dry biomass (292.50% and 370.00%), leaf area (167.97% and 152.84%), shoot length (136.82% and 162.74%), and root length (168.08% and 169.70%) ( Zayed et al, 2017 ). In the same study, IAA supplementation had improved CAT activity (152% and 350%) and PPO (110% and 100%) ( Zayed et al, 2017 ). In another study, potato plants pre-treated with IAA (7 and 14 μM) in vitro under various salt stress levels (0, 40, 60, and 80 mM NaCl) had less oxidative injury than untreated plants due to improved SOD and POD activities ( Khalid and Aftab, 2020 ).…”
Section: Interplay Of Plant Hormones In Conferring Abiotic-induced Ox...mentioning
confidence: 99%